Chromatin structure of simian virus 40-pBR322 recombinant plasmids in COS-1 cells. - Innis, J W (1983)
To study the nucleoprotein structure formed by recombinant plasmid DNA in mammalian cells, nuclei were isolated from COS-1 cells after transfection with a recombinant (pJI1) containing pBR322 sequences and a segment of simian virus 40 containing information for a nuclease-sensitive chromatin structure. The nuclei were incubated with DNase I. DNA fragments which were the size of linear pJI1 DNA were isolated, redigested with restriction enzymes, fractionated by electrophoresis, and detected by hybridization with nick-translated segments prepared from the plasmid DNA. Two DNase I-sensitive sites were detected in the simian virus 40 portion of the plasmid at the same sites that were DNase I sensitive in simian virus 40 chromatin prepared late after infection of African green monkey kidney (BSC-1) cells. One site extended from the viral origin of replication to approximately nucleotide 40. The 21-base pair repeated sequences were relatively DNase I resistant. A second site occurred over the single copy of the 72-base pair segment present in this plasmid. These results indicate that the nuclease-sensitive chromatin structure does not depend on the presence of viral structural proteins. In addition, late viral proteins added to pJI1-transfected COS-1 cells by superinfection with simian virus 40 caused no change in the distribution of DNase I-sensitive sites in plasmid chromatin. Analysis of transfected plasmid DNA may provide a general method applicable to the study of the chromatin structure of cloned segments of DNA.